Functional Literacy and Text Creation - Popovic, Dusanka (European Journal of Social Science Education and Research, 2022)
The results of research about functional literacy (i.e. ability to read, understand and create text and understand its further use), and especially those results that 15-year-olds show in Programme for International Student Assessment (PISA), as well as the importance of this competence for life and work in a modern society, indicate the need for analysis of all the segments that affect its development and improvement. Project How to help students to successfully create oral and written, artistic and non-artistic texts addresses this area in particular. The culture of oral and written expression, as productive language skills, is very interesting to research, and especially to improve. Inseparable from the receptive skills of listening and reading, they are their explicit product. A significant number of theorists and methodologists dealt with this area, but their activity was usually focused on what the teacher needed to do for the students to write well (focused on the process, method, or the result: students' written work). What is unquestionably lacking, but is in the spirit of the changes that we have introduced in our educational system, is dealing with the student as a creator of the text. The observations of methodologists of language and literature teaching prove that this factor in teacher-student-written work conjunction was least dealt with. They point out that the main characteristic of the current literature on the written expression is exaggerated orientation towards written works and neglecting of their authors (creators). The aim of the project was to investigate and recommend the best ways in which to build a functional literacy in the area of successful creation of oral and written text, i.e. to propose a more efficient teaching in the field of oral and written expression. This paper analyzes the opportunities for the development of these areas, providing current educational programs for Mother tongue language and literature in Montenegro, and presents the methodical approach The Creator's path designed as a means of support for all students when creation of text is in question.
Keywords: functional literacy, text creation, oral and written expression, efficient teaching.